Implications of divergence of methionine adenosyltransferase in archaea. Issue 1 (5th November 2021) - Chouhan, Bhanu Pratap Singh; Gade, Madhuri; Martinez, Desirae; Toledo‐Patino, Saacnicteh; Laurino, Paola
Abstract : Methionine adenosyltransferase (MAT) catalyzes the biosynthesis of S‐adenosyl methionine from l ‐methionine and ATP. MAT enzymes are ancient, believed to share a common ancestor, and are highly conserved in all three domains of life. However, the sequences of archaeal MATs show considerable divergence compared with their bacterial and eukaryotic counterparts. Furthermore, the structural significance and functional significance of this sequence divergence are not well understood. In the present study, we employed structural analysis and ancestral sequence reconstruction to investigate archaeal MAT divergence. We observed that the dimer interface containing the active site (which is usually well conserved) diverged considerably between the bacterial/eukaryotic MATs and archaeal MAT. A detailed investigation of the available structures supports the sequence analysis outcome: The protein domains and subdomains of bacterial and eukaryotic MAT are more similar than those of archaea. Finally, we resurrected archaeal MAT ancestors. Interestingly, archaeal MAT ancestors show substrate specificity, which is lost during evolution. This observation supports the hypothesis of a common MAT ancestor for the three domains of life. In conclusion, we have demonstrated that archaeal MAT is an ideal system for studying an enzyme family that evolved differently in one domain compared with others while maintaining the same catalytic activity. Abstract : We investigated archaeal methionine adenosyltransferase (MAT) divergence by structural analysis and ancestral sequence reconstruction. The dimer interface of MAT containing the active site (usually well conserved) diverged considerably between the bacterial/eukaryotic MATs and archaeal MAT. The archaeal MAT ancestor showed substrate specificity, which was lost during evolution, supporting the hypothesis of a common MAT ancestor for the three domains of life.